Screen-printed n-type Si solar cells with laser-doped selective back surface field. (15th May 2021) - Yin, H.P.; Tang, W.S.; Zhang, J.B.; Shan, W.; Huang, X.M.; Shen, X.D.
Highlights: A lean process flow similar to p-PERC cells' is developed for n-PERT cells. The p + emitter and n + BSF are formed in one high-temperature step. The batch average efficiencies of 21.7% and peak value of 21.9% are obtained. Abstract: The primary challenge to the industrial application of n-type silicon solar cells is relatively complicated process flow compared to producing p-type silicon solar cells. This paper demonstrates a simple processing sequence to fabricate n-type silicon solar cells in which the boron-doped emitter and phosphorus-doped back surface field (BSF) are formed in one high-temperature step. By introducing a selective BSF structure that is formed by laser doping, the conversion efficiency of the solar cells can be further improved. The averaged conversion efficiency of 21.7% is obtained in batches with relatively large quantity of cells with tight efficiency distribution.